The effect of forming parameters on the sheet stretch in incremental sheet forming (ISF) process on CNC lathe machine - Moayedfar, Majid; Leman, Zulkiflle; Mirabi, Hamed; Baharudin, B. T. Hang Tuah (Trans Tech Publications, 2013)
The effect of forming parameters during the incremental sheet forming process (ISF) was studied for a circular shape sheet part. ISF is known as a rapid prototyping method to pro-duce sheet metal parts in a batch production series. ISF has found to be useful and advantageous which increases its application in industry. A CNC lathe machine was used in this study because it was easily programmed to move an indenter which worked as the tool, through the sheet metal which was clamped on a plain rounded mold. The work also investigated the influence of some process variables such as spindle speed, tool material; tool feed rate and temperature during the forming procedure. The results showed that a proper spindle speed and tool feed rate at some stage in the forming process improved the surface quality and the rate of penetration.